AI in Healthcare, Oncology, Petroleum, Fraud Detection, and Cybersecurity: Out of the ordinary techniques and new ideas - Hussain, Ibrar (International Journal of Multidisciplinary Sciences and Arts, 2024)
The applicability of AI has increased in multiple industries with increasing opportunities in the areas of healthcare, petroleum, fraud detection and cybersecurity, and cancer medicine. In healthcare, it is helping diagnose ailments, treatments, drug development more effectively and quickly therefore improving patient experience. The same way AI finds application in the exploration, production, and safety of petroleum companies at reduced costs but high efficiency. In fraud detection and cybersecurity in particular, AI is increasing the efficiency of detecting potential threats, predicting potential invasions, and protecting computer networks, providing predictive shield against high risk threats. More so, deep learning is rapidly enhancing cancer diagnosis, creating tailored treatment plans, and speed up drug development to enhance the quality of therapies with better prognosis outcomes. However, current advancements suffer from the following barriers towards a general AI particularly in application; Data privacy issues, Ethical issues and the problem of interdisciplinary collaboration. Nonetheless, the constant further development of AI can be viewed as a great opportunity to solve these problems due to the continuous appearance of new advancements in the sphere of artificial intelligence. AI will remain a key driver of change entering into symbiosis with human knowledge and know-how and having a profound positive effect on healthcare, energy security and beyond, hence transforming and improving lives and economies around the globe.